Ormslev-dyssen – en dysse uden høj? – Fritstående dysser i tragtbægerkulturen - Nielsen, Nina (Kuml, 2003)
The Ormslev Dolmen – a free-standing dolmen? Free-standing dolmens in the Funnel Beaker Culture The Ormslev dolmen – which has the appearance of a free-standing dolmen – is situated near Ormslev Stationsby, west of Aarhus in Jutland (fig. 1). The chamber was excavated for the first time around 1870. In 1975 a second excavation was carried out by Torsten Madsen from Moesgaard Museum, because of the threat from ploughing to the surrounding area. This excavation concentrated on the area east and south of the dolmen, where stones and pottery had been ploughed up. The area north and west of the dolmen was too disturbed – the stone packing around the chamber had totally disappeared. The Ormslev dolmen was erected on a terrace in a sloping piece of land adjacent to an area that lay under water, as part of the Brabrand Fjord, during the Stone Age. The dolmen is situated on a small hillock with its entrance to the east. The chamber consists of six orthostats and two capstones in addition to two, or possibly four, entrance stones (fig. 2). The orthostat furthest from the entrance is 1.5 m in width, the opening about 0.5 m across, and the length of the chamber is 2.4 m. The ground plan of the chamber is thus best described as slightly trapezoid. In front of the chamber entrance – at a distance from it of 3-4 m – a 2 m wide, curving stone packing consisting of one to two layers of hand-to-head sized stones was found (fig. 3). At the time of the excavation this layer was approximately 9 m long, but originally it presumably continued in both directions. No kerbstones or traces of a stone circle were found. Under the stone packing different sorts of pits were found; IA, IB and IC without finds, HY and HZ containing potsherds. Three cooking pits (HV, HW and HX) were also found (fig 2). When the chamber was excavated in the 19th century the finds included a small clay vessel and two flint daggers, all of which can be dated to the early Bronze Age. During the excavation in 1975 some flint artefacts dating to the late Mesolithic and Neolithic appeared in the area outside the chamber. Most of the finds, however, consisted of pottery. In all some 950 potsherds – probably representing 35-40 vessels – were found. The pottery is very fragmented. The surface is in many cases eroded and only a small number of sherds can be pieced together into larger parts or almost entire vessels. The pottery can be divided into an early group dating from the early Middle Neolithic (MNA I-MNA II B perhaps MNA III) i.e. 3300-3000 BC and a late group which primarily dates from the latest part of the Funnel Beaker Culture (MNA IV-V) i.e. 2900-2800 BC, but which also contains a few later potsherds. The early pottery is primarily represented by pedestal bowls, funnel beakers, and carinated vessels. The best preserved vessel is a carinated vessel ornamented with vertical stripes and different motives made of rows of chevrons (fig. 4d) The funnel beakers are of different types, the most remarkable being a very coarsely tempered beaker ornamented with deep circular impressions at the rim and vertical stripes on the belly and at least two thin ritual funnel beakers ornamented with finely incised vertical lines (fig. 4g). Other sherds are decorated with whipped cord, incised or impressed lines and rows of chevrons, and two sherds are decorated with indented impressions. One of the pedestal bowls is decorated with a pattern of cross-hatched rhomboids, and there is a carinated vessel with “hanging” triangles on the shoulder (fig. 4) The late Funnel Beaker pottery consists of funnel-necked bowls, simple bowls and bucket-shaped vessels. The vessels are in several cases very coarsely tempered and have a simple decoration consisting of finger and nail impressions normally placed under or on the rim, as well as finger grooves and horizontal rows of impressions (fig. 5a). In addition two vessels are ornamented with the characteristic “hanging” triangles made of small, fine impressions (fig 5c). All the pottery dates from the latest part of the Funnel Beaker Culture except a sherd with an unusual decoration probably dating from the transition to the Single Grave Culture (MNB, fig. 5d) and a vessel with a distinct foot dating from the Late Neolithic. Fragments of five clay discs, one of them perforated, were also found at the Ormslev dolmen. The discs can possibly be assigned to the late Funnel Beaker Culture, although the dating is somewhat uncertain because of the high degree of fragmentation. The late Funnel Beaker pottery, apart from the distinct-foot vessel and the MNB-sherds, was found spread under or near the stone packing in front of the chamber as well as in the pits HZ and HY. A few early sherds were also found in this area. Most of the early sherds, however, were concentrated in the area just south of the chamber entrance. The pottery found under the stone packing represents a clearing of the chamber which probably took place in the Late Neolithic. The early pottery found south of the entrance, however, represents the sacrificing of vessels during MNA I-II; a common ritual during this period of time. Sherds from the possible transitional MNB vessel and the distinct-foot vessel are found among the early vessels by the chamber entrance. Their appearance in this layer, on the original surface, is striking, and it indicates that no significant sedimentation can have taken place from the MNA I to the Late Neolithic. Another explanation could of course be that the layer covering the early pottery was somehow removed before the later sherds were deposited, but it was not possible to confirm this during the excavation. All traces of the primary burials were gone at the time of the second excavation and the erection of the dolmen can thus only be dated through the earliest pottery – MNA I – which gives an ante quem date of the structure. The megalithic grave was used several times during the Middle Neolithic Funnel Beaker Culture, and as late as the early Bronze Age the dolmen was still used for burials. Most of the dolmens in Denmark have no visible traces, today, of having had barrows over them, and the earth around the chamber only covers the lowest part of the orthostats. Traditionally these dolmens have been explained as structures which have lost their covering mounds because of erosion caused by wind and weather, roots, animals and ploughing. However, the number of free-standing dolmens is much too high to be explained only by erosion or human interference. And as several other observations indicate that free-standing dolmens were in fact a regular type of grave during the Funnel Beaker Culture it is time to reconsider the previous general opinion. First of all the free-standing chambers are not evenly distributed over the country although there does not seem to be any reason for assuming regional differences in the process of barrow destruction. For instance in Djursland a large number of graves of this type can be seen in the landscape. Secondly, in Denmark only dolmens - primarily extended or polygonal ones - are free-standing while the passage graves are always found in barrows. It has been argued that if the destruction of barrows had been caused by natural processes it would be remarkable that it had not affected the passage graves. Although this argument carries conviction it must also be taken into consideration that a passage grave is a much more complex monument than a dolmen and that the differences in the degree of earth-covering therefore in part could be due to the differences in construction. Several dolmens today have absolutely no traces of earth-covering, and because of their situation and other circumstances it is reasonable to believe that they have always been free-standing. This is for instance the case regarding the largest round dolmen in Denmark, Poskær Stenhus, Djursland, and also Stenhuset at Strands, Djursland, which is placed on the top of a hill (fig. 6). Another example is the long-dolmen at Gunderslevholm, Sealand where the kerbstones stand neatly in such a way that if a barrow had once been removed from the dolmen the process would have had to involve thorough cleaning-up of the area between the kerbstones! Finally, free-standing dolmens are a phenomenon known all over Europe where megalithic monuments were built, e.g. the famous Irish portal-tombs (fig. 8). Moreover, the fact that the free-standing megalithic monuments in other countries, for instance England, seem, like those in Denmark, to have a regional distribution, indicates that the distribution itself is significant. The challenge is to prove that dolmens that appear today to be free-standing have in fact never been covered with a barrow. Only a small number of dolmens in Denmark have been scientifically excavated, and just a few of these have been free-standing dolmens; one of these being the Ormslev dolmen. The barrow is usually placed between the chamber and a circle of kerbstones, and the placement of the kerbstones is thus essential in the assessment of a free-standing dolmen. At the Ormslev dolmen it was not possible to find any traces of kerbstones – maybe because they have always been absent. Instead the disposition of pottery outside the chamber turned out to be of great importance. From the fact that late pottery was found within the stone packing and all the way to the entrance stones of the dolmen it can be seen that this area must always have been accessible and cannot have been covered with a mound. If there once was a barrow the kerbstones must therefore have been placed very close to the chamber, with the layer of sacrificed pottery lying outside the kerbstones. A barrow with such a small diameter would have required a solid circle of kerbstones with dry walling. No trace whatsoever of this was found. Finally it should be noted that there may actually not have been sedimentation to the south of the entrance. If this is the case the Ormslev dolmen cannot have been covered with a mound, as soil would then have been washed out and deposited outside the kerbstones. All things considered it is thus reasonable to assume that the Ormslev dolmen was never covered with a barrow. Other excavated dolmens have provided even better examples of free-standing dolmens. The best example from Denmark is one of the Tustrup dolmens in Djursland. From the stratigraphical observations as well as finds of pottery it can clearly be proved that it has never been covered with a mound. Paradoxically, in 1994 the dolmen was reconstructed in such a way that the area between the chamber and the 2 m high kerbstones was filled in with soil (fig. 7). The intention was to restore its “original” appearance as in the Stone Age! At the Sarup area on Funen a number of free-standing dolmens have been excavated. While some proved always to have been free-standing, others had been covered with earth at a later date. This situation can also be observed in cases of other dolmens in Denmark. The later building of barrows is perhaps to be seen in connection with the transition from the building of dolmens to the erection of the closely sealed passage graves. This distinctly marks a change in mortuary practice and it is possible that at the time when closed chambers became the prevailing way of building megalithic monuments some of the originally free-standing dolmens were covered with earth. Also outside Denmark excavations of megalithic monuments have proved that the chambers were originally free-standing, for instance the Trollasten dolmen in Scania, Sweden, or most of the megalithic chambers at the Carrowmore cemetery in North-western Ireland. All these indications, arguments, and not least well-documented examples of free-standing megalithic monuments – in Denmark as well as in other parts of Europe – justify the conclusion that free-standing dolmens were a regular type of grave during the Funnel Beaker Culture. Nina Nielsen Afdeling for Forhistorisk Arkæologi Aarhus Universitet Moesgård